2018
DOI: 10.1002/ijc.31605
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NKILA suppresses TGF‐β‐induced epithelial–mesenchymal transition by blocking NF‐κB signaling in breast cancer

Abstract: TGF-β plays a central role in mediating epithelial-mesenchymal transition (EMT) by activating the Smad pathway. In addition, accumulating evidence suggests that TGF-β-induced EMT is NF-κB-dependent in various cancer types. However, it is largely unclear if NF-κB mediates TGF-β-induced EMT in breast cancer, and if this mediation occurs, the regulatory mechanisms are unknown. In our study, we found that TGF-β activates the NF-κB pathway. Inhibition of NF-κB signaling markedly abrogates TGF-β-induced EMT. By stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 55 publications
6
67
0
Order By: Relevance
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse . Cells undergoing EMT are known to acquire stem cell‐like properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse . Cells undergoing EMT are known to acquire stem cell‐like properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that stimulating EMT and increasing CSCs can promote cancer metastasis and relapse. 34,[47][48][49][50] Cells undergoing EMT are known to acquire stem cell-like properties. Loss of epithelial marker E-cadherin, increased expression of mesenchymal markers Fibronectin and Vimentin and the EMT regulator Snail, which are important events in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…346 Activation of TGF-β1 induces lncRNA NKILA expression to block NF-κB signaling, which inhibits metastasis of breast CSCs. 412 TGF-β also directly regulates the expression of Wnt5a in breast CSCs to limit the stem cell population. 413 Furthermore, Notch, IKK/NF-κB, and other pathways together regulate the proliferation and metastasis of CD133 + cutaneous SCC stem cells.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…Notch signaling was also proved to promote HER2 + breast cancer cell proliferation and stem cell survival. [40][41][42] However, we future molecular and large scale, multicenter studies should be designed to analyze the exact mechanisms that USP8 regulate the proliferation of BC. Meanwhile, lots of studies have shown that epithelial-mesenchymal transition played an important role in the progression of BC.…”
Section: Discussionmentioning
confidence: 99%